STUDI ALIENASI KARAKTER RASKOLNIKOV DALAM NOVEL CRIME AND PUNISHMENT KARYA FYODOR DOSTOEVSKY - Fairuz Quamilla Hilmina; Ninuk Sholikhah Akhiroh (Universitas Negeri Makassar, 2025)
This study aims to analyze the alienation of the character Raskolnikov in Fyodor Dostoevsky’s novel Crime and Punishment. It adopts Melvin Seeman’s five dimensions of alienation powerlessness, meaninglessness, normlessness, isolation, and self-estrangement. Using an interpretative qualitative approach and content analysis techniques, the data, consisting of narrative excerpts representing symptoms of social alienation, are analyzed according to their contextual occurrences in the story. The novel is read as a text that records the failure of the social system to provide spaces for meaning, control, and identity. The setting of St. Petersburg in the novel, though fictional, is constructed as a depiction of a harsh, unequal, and dehumanized modern world. The findings indicate that Raskolnikov’s alienation is not merely a psychological symptom but a manifestation of structural inequalities that erode human subjectivity. The study underlines the significance of literature as a medium for critical reflection on social reality.